The Relationship Between Service Quality, Access to Information, Cost Savings to The Satisfaction of Outpatient Poly Patients at Abdoel Wahab Sjahranie Hospital - Muksin Muksin; Ulia Fitri; Andik Supriyatno (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
The quality of service is very important, because if the service is good, patient satisfaction will have a positive effect on the hospital as well. This type of research is an analytical survey with a cross-sectional research design, that is, research where data is collected only once to answer research problems. The population of this study was outpatients at Abdoel Wahab Sjahranie Hospital during the study period. The study population through the average number of visits per month was 470 people, so the study sample was 212 people. The quality of service is related to the satisfaction of outpatients at Abdoel Wahab Sjahranie Hospital by prioritizing the ability of health personnel, courtesy, comfort, convenience, speed, and suitability of services. As a recommendation, Abdoel Wahab Sjahranie Hospital maintains a good Quality of Service and then improves access to information and actualizes cost savings through an organized work plan.